The Sanctity of the Seventh Year : A Study of Mishnah Tractate Shebiit - Newman, Louis E., 1956- (Book collections on Project MUSE., 2020)
"This study is a translation and exegesis of Tractate Shebiit (The Sabbatical Year) in Mishnah and in its corresponding document, Tosefta. The goal of this volume is to explain the laws of this tractate as they were understood by those who redacted the document in Palestine in the late second century C.E."--Provided by publisher